Modular Reconfigurable DNA Origami: From Two‐Dimensional to Three‐Dimensional Structures. (13th October 2020) - Liu, Yan; Cheng, Jin; Fan, Sisi; Ge, Huan; Luo, Tao; Tang, Linlin; Ji, Bin; Zhang, Chuan; Cui, Daxiang; Ke, Yonggang; Song, Jie
Abstract: DNA origami enables the manipulation of objects at nanoscale, and demonstrates unprecedented versatility for fabricating both static and dynamic nanostructures. In this work, we introduce a new strategy for transferring modular reconfigurable DNA nanostructures from two‐dimensional to three‐dimensional. A 2D DNA sheet could be modularized into connected parts (e.g., two, three, and four parts in this work), which can be independently transformed between two conformations with a few DNA "trigger" strands. More interestingly, the transformation of the connected 2D modules can lead to the controlled, resettable structural conversion of a 2D sheet to a 3D architecture, due to the constraints induced by the connections between the 2D modules. This new approach can provide an efficient mean for constructing programmable, higher‐order, and complex DNA objects, as well as sophisticated dynamic substrates for various applications. Abstract : We demonstrated a new strategy for constructing modular DNA nanostructures that are reconfigurable from two‐dimensional to three‐dimensional. This strategy demonstrates an efficient means for constructing programmable, higher‐order, and complex DNA objects, as well as sophisticated dynamic substrates for various applications.